Animal Organ Donors: Human Health Applications - Platt, Jeffrey L.; Prather, Randall S. (Council for Agricultural Science and Technology (CAST), 2004)
This issue paper examines current and future concerns and benefits for using animals as organ and tissue donors (xenotransplantation). The authors provide a careful review of the procedure’s history and development, as well as an outline of possible applications for the future as xenotransplantation impacts human health.